An integrative system biology approach to delineate complex genotype-phenotype associations in Autism Spectrum Disorder - Asif, M (2017)
Introduction: Autism Spectrum Disorder (ASD) is characterized by deficits in social interaction and communication, and by the presence of repetitive behavior and/or restricted interests. ASD manifests with heterogeneous phenotype and has an estimated global prevalence of ~1%;- ASD is difficult to diagnose in very young children. Delayed diagnosis leads to delay in applying behavioral therapies that may help to reduce symptoms, particularly when applied at young age; - Copy Number Variant (CNV) screening has been widely used for primary diagnosis purposes and is associated with phenotypic variability in ASD patients; - Large scale studies have identified hundreds of ASD implicated loci; however, mechanistic and clinical interpretation of these disease-causing variants remains elusive.